Die relatiewe belangrikheid van verskillende evalueringskriteria by die koop van 'n passasiersvoertuig: 'n Vergelykende studie van mans en vroue - P. J. Du Plessis; C. Boshoff (South African Journal of Business Management, 1988)
– A number of studies revealed that the role of women both as influencer and independent decision-maker is becoming increasingly important in the buying decision involving the purchase of a passenger vehicle. In today's highly competitive South-African motor vehicle market it is becoming vital that motor manufacturers pay greater attention to market needs - specially with regard to important market segments. This study analyses certain aspects of the market segment consisting of women. The null-hypothesis this study tested was that there are no differences between male and female consumers pertaining to the relative importance of evaluation criteria, when purchasing a passenger vehicle. By means of analysis of variance it was established that there are significant differences (P 0,01) between men and women with regard to 15 of the 65 evaluation criteria. It was also found that there are 50 insignificant differences between the two groups. The hypothesis, as formulated is thus rejected, with regard to 15 of the evaluation criteria, in favour of the alternate hypothesis.
Keywords: 650